Understanding the new super consumer (mom and kids) - Coffey, Tim (Henry Stewart Talks, 2010)
There is a new mom on the block, Smart moms, Time starved and money starved, New kid on the block, Kid influence on items bought for children and the family, Why market to the super consumer?, How to market to the super consumer?, Use the right media, Mom and kid motives, Not all kids are alike, Motivational platforms, Kid creative